2020
DOI: 10.1016/j.gie.2020.04.049
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 polymerase chain reaction testing before endoscopy: an economic analysis

Abstract: Background and Aims: The novel coronavirus disease 2019 (COVID-19) pandemic has limited endoscopy utilization, causing significant health and economic losses. We aim to model the impact of polymerase chain reaction (PCR) testing into resuming endoscopy practice. Methods: We performed a retrospective review of endoscopy utilization during the COVID-19 pandemic for a baseline reference. A computer model compared 3 approaches: strategy 1, endoscopy for urgent indications only; strategy 2, testing for semiurgent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
73
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 17 publications
1
73
0
5
Order By: Relevance
“…Patients who were later diagnosed with COVID were more likely to have outpatient procedures compared to patients who were already known to have COVID, so it is important not to limit testing to inpatients. Economic analysis has suggested that universal pre-endoscopy COVID PCR testing is a cost-effective strategy for reopening endoscopy units, and our findings add further weight to this policy, which has already been implemented in many centers [13]. In addition to screening for COVID, we suggest providers use of N95 respirators and face shields in addition to standard personal protective equipment, restrict the number of unnecessary personnel, and carefully weigh the risks and benefits of endoscopic procedures, in order to limit transmission of coronavirus as much as possible.…”
Section: Discussionsupporting
confidence: 54%
“…Patients who were later diagnosed with COVID were more likely to have outpatient procedures compared to patients who were already known to have COVID, so it is important not to limit testing to inpatients. Economic analysis has suggested that universal pre-endoscopy COVID PCR testing is a cost-effective strategy for reopening endoscopy units, and our findings add further weight to this policy, which has already been implemented in many centers [13]. In addition to screening for COVID, we suggest providers use of N95 respirators and face shields in addition to standard personal protective equipment, restrict the number of unnecessary personnel, and carefully weigh the risks and benefits of endoscopic procedures, in order to limit transmission of coronavirus as much as possible.…”
Section: Discussionsupporting
confidence: 54%
“… 1 The authors conclude that PCR testing is an effective strategy to be implemented during the recovery phase. 1 …”
mentioning
confidence: 95%
“…We read the timely article by Corral et al 1 on the economic analysis of COVID-19 polymerase chain reaction (PCR) testing before endoscopy with great interest. After initially choosing to postpone elective procedures, healthcare facilities are seeking strategies to safely resume endoscopy to address the growing list of waiting patients.…”
mentioning
confidence: 99%
See 2 more Smart Citations